Protein dysregulation during Leishmania infantum infection in anti-TNF immunosuppressed mice revealed through quantitative proteomics analysis of extracellular vesicles - Bernardo, Lorena; Montero-Calle, Ana; Solana, Jose Carlos; Lozano-Rendal, Marina; Torres, Ana; Sánchez, Carmen; Barderas, Rodrigo; Moreno, Javier; Carrillo, Eugenia (Frontiers in Immunology, 2025)
IntroductionVisceral leishmaniasis (VL) occurs more frequently in immunosuppressed individuals, especially those undergoing immunosuppressive drug therapy for an autoimmune disease. In those receiving TNF antagonist therapy (anti-TNF), the course of VL is more severe and the response to traditional leishmanicidal treatments, such as antimonials (Sb), is often reduced. This effect of anti-TNF treatment is observed in our immunosuppressed-mouse model of VL. In this model, we compared anti-TNF immunosuppression with no immunosuppression before and after VL treatment with Sb.MethodsSerum-derived extracellular vesicles (EVs) were analyzed through label-free quantitative proteomics to identify proteins involved in both VL severity and the impact of anti-TNF immunosuppression on treatment outcome.ResultsIn total, 223 dysregulated proteins were found in the pre-treatment groups, the majority of which, such as vitronectin, haemopexin or caveolin-1, were downregulated in the anti-TNF samples. In contrast, 173 proteins were identified in the Sb-treatment groups, most of which were found enriched in the anti-TNF plus treatment samples (anti-TNF+Sb) including fibronectin, transferrin, vitronectin and dipeptidyl peptidase-4. These differentially-expressed proteins were associated with pathways related to the immune system, liver regeneration, and ion transport.ConclusionOur findings have useful implications for the clinical management of VL patients under anti-TNF immunosuppression.